Formation of scientific research competence of future engineers-pedagoges of higher educational institutions - Paiunova, A. (Problems of Engineer-Pedagogical Education, 2018)
The research is devoted to the topical issue which is the development of scientific research competence of future engineers-teachers of higher educational establishments. The article presents the results of the pilot study among the 2nd and 3rd year students at the Educational Scientific Professional-Pedagogical Institute of Ukrainian Engineering and Pedagogical Academy (Bakhmut). The basic objectives of research activity of future engineers-teachers at higher educational institutions are defined in the present work. The author regards students’ research competence as a process of mastering professional competences, and suggests conditions for improving the process of developing future engineers-teachers’ relevant skills. The article also presents the structure of scientific research competence of future engineers-teachers of higher educational institutions. A number of problems, which occur at different stages and impede the effective organization of students’ research activity, have been investigated, namely material, technical, psychological and pedagogical, scientific and methodological.